Systemic Approach to Learning Terms: Typology of Economic Terms - Anvarоnva, Mansurоva Nоdira (International Journal on Integrated Education, 2023)
This work is devoted to the study of demonstrating in what way the systemic approach to the study of economic terms solves certain teaching-learning problems. Knowledge has a systemic nature. The systemic nature of knowledge is revealed through a system of concepts or phenomena, which, in their turn, are expressed through a system of terms. The systemic nature of the term can be viewed both from the point of view of the expression plane and from the point of view of the content plane (e.g. monosemantic/ polysemantic terms; key/peripheral terms; abstract/ concrete terms; borrowed/ native terms; metaphor-based terms, etc.) and from the point of view of their functioning (national/ regional/ international). The systemic characteristics of economic terms are numerous, and all of them should be considered in detail if academic success is a desired outcome.